Metabolic memory underlying minimal residual disease in breast cancer - Radić Shechter, Ksenija; Kafkia, Eleni; Zirngibl, Katharina; Gawrzak, Sylwia; Alladin, Ashna; Machado, Daniel; Lüchtenborg, Christian; Sévin, Daniel Charles; Brügger, Britta; Patil, Kiran Raosaheb; Jechlinger, Martin (Molecular systems biology, 2021)
Tumor relapse from treatment-resistant cells (minimal residual disease, MRD) underlies most breast cancer-related deaths. Yet, the molecular characteristics defining their malignancy have largely remained elusive. Here, we integrated multi-omics data from a tractable organoid system with a metabolic modeling approach to uncover the metabolic and regulatory idiosyncrasies of the MRD. We find that the resistant cells, despite their non-proliferative phenotype and the absence of oncogenic signaling, feature increased glycolysis and activity of certain urea cycle enzyme reminiscent of the tumor. This metabolic distinctiveness was also evident in a mouse model and in transcriptomic data from patients following neo-adjuvant therapy. We further identified a marked similarity in DNA methylation profiles between tumor and residual cells. Taken together, our data reveal a metabolic and epigenetic memory of the treatment-resistant cells. We further demonstrate that the memorized elevated glycolysis in MRD is crucial for their survival and can be targeted using a small-molecule inhibitor without impacting normal cells. The metabolic aberrances of MRD thus offer new therapeutic opportunities for post-treatment care to prevent breast tumor recurrence.
Gesehen am 28.01.2022